Pandemia, Poznań, 1918-1920 - Kurek, Krzysztof (Wydawnictwo Poznańskie Studia Polonistyczne, 2021)
The article discousses the depicitions of the Spanish Flu pandemic from 1918-1920 in Poznan press. The author places his considerations in the broad social and cultural context of kontemporary knowledge about flu, presents the theories on the origins of the pandemic and comments on the medical publications from the 1918-1920 period. Screening the press from the period, easily noticeable becomes the relatively low number (compared with the number of infections and deaths) of reports on the Spanish flu that failed to present the true scale of the danger. The image of reality presented in the press of that period was dminated by current politics, situation on the war fronts, social and economic challenges, food supplies to civilians and the ending of World War I. The common experience od death and illness due to warfare resulted in lack of dramatic reactions of the press.
Keywords: Spanish Flu pandemic; pandemics of infectious diseases in the 20th century; social and cultural history of infectious diseases; image of Spanish Flu pandemic in Poznan press; pandemia hiszpańskiej grypy w Polsce 1918-1920; społeczna i kulturowa historia epidemii; obraz pandemii hiszpanki w prasie poznańskiej